Beta-Lactam Antibiotics as A Possible Novel Therapy for Managing Epilepsy and Autism, A Case Report and Review of Literature - GHANIZADEH*, Ahmed; BERK, Michael (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Ghanizadeh A, Berk M. Beta-Lactam Antibiotics as A Possible Novel Therapy for Managing Epilepsy and Autism, A Case Report and Review of Literature. Iran J Child Neurol. 2015 Winter;9(1):99-102. Abstract Autism is a disorder of unknown etiology. There are few FDA approved medications for treating autism. Co-occurring autism and epilepsy is common, and glutamate antagonists improve some symptoms of autism. Ceftriaxone, a beta-lactam antibiotic, increases the expression of the glutamate transporter 1 which decreases extracellular glutamate levels. It is hypothesized that modulating astrocyte glutamate transporter expression by ceftriaxone or cefixime might improve some symptoms of autism. This case report of a child with autism and epilepsy suggests a decrease in seizures after taking cefixime. References Selassie AW, Wilson DA, Martz GU, Smith GG, Wagner JL, Wannamaker BB. Epilepsy beyond seizure: a population-based study of comorbidities. Epilepsy Res 2014;108(2): 305-315. Sansa G, Carlson C, Doyle W, Weiner HL, Bluvstein, Barr W, et al. Medically refractory epilepsy in autism. Epilepsia 2011; 52(6): 1071-1075. Ghanizadeh A. Increased glutamate and homocysteine and decreased glutamine levels in autism: a review and strategies for future studies of amino acids in autism. Dis Markers; 2013;35(5): 281-286. Yamada T, Kawahara K, Kosugi T, Tanaka M.Nitric oxide produced during sublethal ischemia is crucial for the preconditioning-induced down-regulation of glutamate transporter GLT-1 in neuron/astrocyte co-cultures. Neurochem Res 2006:31(1): 49-56. Zeng, LH, Ouyang Y, Gazit V, Cirrito JR, Jansen LA, Ess KC, et al. Abnormal glutamate homeostasis and impaired synaptic plasticity and learning in a mouse model of tuberous sclerosis complex. Neurobiol Dis 2007; 28(2): 184-196. Zeng LH, Bero AW, Zhang B, Holtzman D. M. , Wong M. Modulation of astrocyte glutamate transporters decreases seizures in a mouse model of Tuberous Sclerosis Complex. Neurobiol Dis 2010; 37(3): 764-771. Nizzardo M, Nardini M, Ronchi D, Salani S, Donadoni C, Fortunato F, et al. Beta-lactam antibiotic offers neuroprotection in a spinal muscular atrophy model by multiple mechanisms. Experimental Neurology 2011; 229: 214–225. Harada M, Taki MM, Nose A, Kubo H, Mori K, Nishitani H and T. Matsuda. Non-Invasive Evaluation of the GABAergic/Glutamatergic System in Autistic Patients Observed by MEGA-Editing Proton MR Spectroscopy Using a Clinical 3 Tesla Instrument. J Autism Dev Disord 2010 Apr;41(4):447-54. doi: 10.1007/s10803-010-1065- 0. Polleux, F. and J. M. Lauder. Toward a developmental neurobiology of autism. Ment Retard Dev Disabil Res Rev 2004;10(4): 303-317. Maezawa I, Jin LW. Rett syndrome microglia damage dendrites and synapses by the elevated release of glutamate. J Neurosci 2010;30(15): 5346-5356. Ghanizadeh A. Targeting neurotensin as a potential novel approach for the treatment of autism. J Neuroinflammation 2010;7(1): 58. Ghanizadeh A. Transplantation of GABAergic cell line as a novel hypothesized treatment for autism. Epilepsy & Behavior 2010;19(4): 664. Kim SY, Jones TA. The effects of ceftriaxone on skill learning and motor functional outcome after ischemic cortical damage in rats. Restor Neurol Neurosci 2013;31(1):87-97. doi: 10.3233/RNN-2012-120245. Ghanizadeh A.Could fever and neuroinflammation play a role in the neurobiology of autism? A subject worthy of more research. Int J Hyperthermia 2011;27(7): 737-738. Ghanizadeh A. May lovastatin target both autism and epilepsy? A novel hypothesized treatment. Epilepsy Behav 2011;20(2): 422. Ghanizadeh A. Hydrogen as a novel hypothesized emerging treatment for oxidative stress in autism. Eur Rev Med Pharmacol Sci 2012;16(9): 1313-1314. Ghanizadeh A. Physical exercise and intermittent administration of lactulose may improve autism symptoms through hydrogen production. Med Gas Res 2012;2(1): 19. Asadabadi M, Mohammadi MR, Ghanizadeh A, Modabbernia A, Ashrafi MR, Hassanzadeh E, et al. Celecoxib as adjunctive treatment to risperidone in children with autistic disorder: a randomized, double-blind, placebo-controlled trial. Psychopharmacology (Berl) 2013 Jan;225(1):51-9. doi: 10.1007/s00213-012- 2796-8. Epub 2012 Jul 11. Wang DD, Englot DJ, Garcia PA, Lawton MT, Young WL. Minocycline- and tetracycline-class antibiotics are protective against partial seizures in vivo. Epilepsy Behav 2012;24(3): 314-318. Librizzi L, Noe F, Vezzani A, Curtis M, Ravizza T. Seizure-induced brain-borne inflammation sustains seizure recurrence and blood-brain barrier damage. Ann Neurol 2012;72(1): 82-90. Gasior MK, Nieoczym SD, Wlaz P. Clavulanic acid does not affect convulsions in acute seizure tests in mice. J Neural Transm 2012;119(1): 1-6. Beheshti Nasr SM, Moghimi A, M. Mohammad-Zadeh M, Shamsizadeh A and Noorbakhsh SM. The effect of minocycline on seizures induced by amygdala kindling in rats. Seizure 2013;22(8): 670-674. Erickson CA, Posey DJ, Stigler KA, Mullett J, Katschke AR,McDougle CJ. A retrospective study of memantine in children and adolescents with pervasive developmental disorders. Psychopharmacology (Berl) 2007;191(1): 141-147. Thabet F, Al Maghrabi M, Al Barraq A, Tabarki B. Cefepime-induced nonconvulsive status epilepticus: case report and review. Neurocrit Care 2009;10(3): 347-351.